Aplikasi Metode Gravity Dengan Data Satelit Untuk Identifikasi Struktur Bawah Permukaan (Studi Kasus Semenanjung Muria) - Hilda Ayu Noor Aulia Anisa; Rina Dwi Indriyana; Muhammad Irham (Youngster Physics Journal, 2018)
Mass distribution beneath  Muria Peninsula was conducted with gravity methods to describe the subsurface mass distribution of the Muris peninsula. Anomalous data obtained from bgi.omp.obs. 3D modeling using Grablox and Bloxer software. 3D modeling results obtained five incisions consisting of two Eastern-directed incisions to the West, and three incisions pointing north to the South. The modeling results indicate a fault in the north of the study area and trails East to West, and a fault that extends over the Muria Mountain, north to south direction. Muria Basin with density of rock type 2.0 g / cc to 2.35 g / cc. The area is due to the sedia- tion of the muria peninsular, and the form of the continuous basin of Javanese anticlorium.Keywords: Gravity Method, density, gradient analysis, upward continuation, 3D modelling